Parental Preferences and Non-Spatial Factors Influencing Home-to-school Distance in Urban India: Insights From Visakhapatnam - Rohinikumar Reddy; Ram Sateesh Pasupuleti (Alanya Üniversitesi, 2024)
The school in the neighbourhood unit has been a significant and irreplaceable element in promoting active school commutes, and physical activity needs for children. However, urban areas in India are currently witnessing long school commutes. This study explores parental preferences for school selection in an urban Indian context, focusing on non-spatial attributes of schools associated with home-to-school distance. A questionnaire-based cross-sectional survey was conducted in Visakhapatnam, Andhra Pradesh, with a sample size of 409 families. Data were collected under four parameters: family demographics, socio-economics, neighbourhood environment, and non-spatial attributes of the schools. Pearson's chi-square (χ2) test of independence was adopted to identify the association between the dependent and predictor variables. Further, a multinomial logistic regression model was employed to predict the odds in home-to-school distance. These methods were chosen for their ability to provide robust and reliable results. The findings, which indicate that child age, number of school-going children, annual household income, school's board of affiliation, and education level significantly predict home-to-school distance, have practical implications. They suggest that policy interventions aimed at reducing school commute times should consider these non-spatial factors. Enhancing local school attributes could encourage shorter commutes, promoting healthier lifestyles for children. This understanding can guide the development of policies and interventions that effectively reduce school commute times.